Identification and Characterization of Three Epithiospecifier Protein Isoforms in Brassica oleracea - Witzel, Katja; Abu Risha, Marua; Albers, Philip; Börnke, Frederik; Hanschen, Franziska S. (Frontiers in Plant Science, 2019)
Glucosinolates present in Brassicaceae play a major role in anti-herbivory defense. Upon tissue disruption glucosinolates come into contact with myrosinase, which initiates their breakdown to biologically active compounds. Among these, the formation of epithionitriles is triggered by the presence of epithiospecifier protein (ESP) and a terminal double bond in the glucosinolate side chain. While one ESP gene is characterized in the model plant Arabidopsis thaliana (AtESP; At1g54040.2), Brassica species underwent genome triplication since their divergence from the Arabidopsis lineage. This indicates the presence of multiple ESP isoforms in Brassica crops that are currently poorly characterized. We identified three Brassica oleracea ESPs, specifically BolESP1 (LOC106296341), BolESP2 (LOC106306810) and BolESP3 (LOC106325105) based on in silico transcriptome analysis. Transcript and protein abundance was assessed in shoots and roots of four B. oleracea vegetables, namely broccoli, kohlrabi, white and red cabbage, because these genotypes showed a differential pattern for the formation of glucosinolate hydrolysis products as well for their ESP activity. BolESP1 and BolESP2 were expressed mainly in shoots, while BolESP3 was abundant in roots. Biochemical characterization of heterologous expressed BolESP isoforms revealed different substrate specificities towards seven glucosinolates: all isoforms showed epithiospecifier activity on alkenyl glucosinolates, but not on non-alkenyl glucosinolates. The pH-value differently affected BolESP activity: while BolESP1 and 2 activities were optimal at pH 6-7, BolESP3 activity remained relatively stable from pH 4 to 7. In order test their potential for the in vivo modification of glucosinolate breakdown, the three isoforms were expressed in A. thaliana Hi-0, which lacks AtESP expression, and analyzed for the effect on their respective hydrolysis products. The BolESPs altered the hydrolysis of allyl glucosinolate in the A. thaliana transformants to release 1-cyano-2,3-epithiopropane and reduced formation of the corresponding 3-butenenitrile and allyl isothiocyanate. Plants expressing BolESP2 showed the highest percentage of released epithionitriles. Given these results, we propose a model for isoform-specific roles of B. oleracea ESPs in glucosinolate breakdown.